Agency and Affordances in Study Abroad - Andrew D. Tweed; Hayo Reinders (Education Sciences, 2023)
Research in study abroad (SA) has developed over the past several decades, with an increasing focus on individual learners and their experiences. Despite this trend, it remains unclear what affordances beyond the classroom are available to students and whether and how learners enact their agency to make use of the available opportunities. The present study adopts an ecological framework to examine how four Japanese learners enacted their agency to capitalize on affordances for language learning beyond the classroom during study abroad. Agency is understood as a multidimensional construct, with both internal and external dimensions. Learners utilized a smartphone application to regularly report their language use and associated reflections. Further details about their experiences were elicited by post-study abroad questionnaires and interviews. The findings reveal the various kinds of language episodes reported by the students and how these learners exercised their agency in relation to their learning experiences. A discussion of what factors likely contributed to these learners’ enacting their agency is included. The study concludes with implications for supporting students’ out-of-class learning during study abroad.